A sequential approach for achieving separate sensible and latent cooling. (September 2020) - Ma, Jie; Horton, W. Travis
Highlight: Propose a sequential separate sensible and latent cooling (SSLC) system. The SSLC approach applies variable speed compressor and fan technology. Develop a validated numerical SSLC model for SSLC performance prediction. Significant potential energy savings can be achieved by wise application. Abstract: Separate sensible and latent cooling (SSLC) is a potentially beneficial approach to improve the efficiency of air conditioning systems; however, the complex configuration of existing and proposed SSLC systems increases installation and maintenance costs, limiting their widespread use in new construction and building retrofit opportunities. In this paper, a sequential SSLC system is proposed to realize the separation of sensible and latent loads by switching a single vapor compressor cycle between two modes (low-SHR and sensible only). This effect is achieved by applying readily available variable-speed equipment at a high compressor speed and a low fan speed to achieve the low-SHR mode operating for dehumidification. This is followed by a sensible only mode to cool the air, which is achieved through a low compressor speed and a high evaporator fan speed. To predict the performance of a sequential SSLC system, a numerical model has been developed and validated. Using this numerical model for energy consumption and optimization studies, it is found that the sequential SSLC system has the potential to save 6.9% to 11.5% energy compared to a traditional cooling system.